2022
DOI: 10.1097/rli.0000000000000866
|View full text |Cite
|
Sign up to set email alerts
|

New-Generation Low-Field Magnetic Resonance Imaging of Hip Arthroplasty Implants Using Slice Encoding for Metal Artifact Correction

Abstract: ObjectivesDespite significant progress, artifact-free visualization of the bone and soft tissues around hip arthroplasty implants remains an unmet clinical need. New-generation low-field magnetic resonance imaging (MRI) systems now include slice encoding for metal artifact correction (SEMAC), which may result in smaller metallic artifacts and better image quality than standard-of-care 1.5 T MRI. This study aims to assess the feasibility of SEMAC on a new-generation 0.55 T system, optimize the pulse protocol pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 33 publications
0
15
1
Order By: Relevance
“…During quantitative artifact assessment, the lowest artifact intensities were observed for the Ti implant at 1.5 T. This contrasts previous investigations, e.g., the study of Matsuura et al, who demonstrated less artifacts for neurosurgical biomaterials at 0.5 T compared to 1.5 T and 3 T [20,21]. This discrepancy might be explained by substantial differences in technical specifications of the scanner systems used.…”
Section: Discussioncontrasting
confidence: 81%
“…During quantitative artifact assessment, the lowest artifact intensities were observed for the Ti implant at 1.5 T. This contrasts previous investigations, e.g., the study of Matsuura et al, who demonstrated less artifacts for neurosurgical biomaterials at 0.5 T compared to 1.5 T and 3 T [20,21]. This discrepancy might be explained by substantial differences in technical specifications of the scanner systems used.…”
Section: Discussioncontrasting
confidence: 81%
“…In the mid‐field range, Khodarahmi et al compared artifacts in 0.55T and 1.5T imaging of patients with hip implants. They found a 45%–64% reduction in image artifact when using 0.55T compared to 1.5T, even when 1.5T scanners used a slice encoding for metal artifact correction protocol, though there was a modest 17%–28% reduction in SNR at 0.55T 167 …”
Section: Musculoskeletal Imagingmentioning
confidence: 99%
“…They found a 45%-64% reduction in image artifact when using 0.55T compared to 1.5T, even when 1.5T scanners used a slice encoding for metal artifact correction protocol, though there was a modest 17%-28% reduction in SNR at 0.55T. 167 Another challenge at low-field is fat suppression, which increases contrast when evaluating cartilage, menisci, or bone marrow. 168 Many fat suppression techniques rely on the chemical shift between lipids and water, which is proportional to magnetic field strength.…”
Section: Musculoskeletal Imagingmentioning
confidence: 99%
“…We applied the cable coil concept to knee MRI, which is the most widely accepted imaging tool for diagnosing various knee injuries 32 . Amidst the pursuit of faster scan time and better SNR, many advantages of low-field MRI systems (< 1.0 T) for musculoskeletal radiology, such as reduced metal artifacts 33 are often overlooked. Recently, a new-generation whole-body 0.55 T MRI system has been cleared by the FDA for clinical imaging 34 , 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a new-generation whole-body 0.55 T MRI system has been cleared by the FDA for clinical imaging 34 , 35 . The system can offer some of the advantages of dedicated extremity scanners such as greater accessibility due to lower cost compared to high-field systems, improved patient comfort given its 80-cm wide bore, as well as reduced susceptibility artifacts and specific absorption rate 33 .…”
Section: Discussionmentioning
confidence: 99%